2021
DOI: 10.1186/s13068-021-01972-4
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic evaluation of microalgae high-density liquid fuel production at 12 international locations

Abstract: Background Microalgae-based high-density fuels offer an efficient and environmental pathway towards decarbonization of the transport sector and could be produced as part of a globally distributed network without competing with food systems for arable land. Variations in climatic and economic conditions significantly impact the economic feasibility and productivity of such fuel systems, requiring harmonized technoeconomic assessments to identify important conditions required for commercial scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…According to LCA studies by Ketzer et al, 119 a vast variation of energy return on investment (EROI) ranges from 0.01 to 3.35, and energy input optimization in cultivation, harvesting, and downstream processing was required to make the biorefinery process profitable, and the difficulties in LCA of heterotrophic algae and yeast were the lack of data on industrial-scale production, especially for the feedstock processing and cultivation. 120 Roles et al 121 adopted a validated Techno-economic and Life Cycle Analysis (TELCA) (Figure 8) to compare the performance of • High biomass production and antioxidant capability of biomass were achieved using a mesh ultrathin layer photobioreactor. 122 • This new bioreactor led to a high environmental impact on the biomass production, while a lower environmental impact on the antioxidant production was observed.…”
Section: Life Cycle Assessment (Lca) Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to LCA studies by Ketzer et al, 119 a vast variation of energy return on investment (EROI) ranges from 0.01 to 3.35, and energy input optimization in cultivation, harvesting, and downstream processing was required to make the biorefinery process profitable, and the difficulties in LCA of heterotrophic algae and yeast were the lack of data on industrial-scale production, especially for the feedstock processing and cultivation. 120 Roles et al 121 adopted a validated Techno-economic and Life Cycle Analysis (TELCA) (Figure 8) to compare the performance of • High biomass production and antioxidant capability of biomass were achieved using a mesh ultrathin layer photobioreactor. 122 • This new bioreactor led to a high environmental impact on the biomass production, while a lower environmental impact on the antioxidant production was observed.…”
Section: Life Cycle Assessment (Lca) Studiesmentioning
confidence: 99%
“…According to LCA studies by Ketzer et al, a vast variation of energy return on investment (EROI) ranges from 0.01 to 3.35, and energy input optimization in cultivation, harvesting, and downstream processing was required to make the biorefinery process profitable, and the difficulties in LCA of heterotrophic algae and yeast were the lack of data on industrial-scale production, especially for the feedstock processing and cultivation . Roles et al adopted a validated Techno-economic and Life Cycle Analysis (TELCA) (Figure ) to compare the performance of algal biodiesel production in 12 locations under various climatic and economic settings. The capital expenditure (CAPEX) and annual OPEX for these 12 facilities with a size of 500 ha were US$ 128–245 million and US$ 7.7–16.4 million, respectively.…”
Section: Life Cycle Assessment (Lca) Studiesmentioning
confidence: 99%
“…The analysis revealed that a minimum diesel selling price below US$1.85 L −1 and a profitable internal rate of return of up to 22.1% could be achieved at ten locations. [ 91 ]…”
Section: Techno‐economic Viability Of Microalgal Biorefineriesmentioning
confidence: 99%
“…The analysis revealed that a minimum diesel selling price below US$1.85 L −1 and a profitable internal rate of return of up to 22.1% could be achieved at ten locations. [91] Microalgal biorefinery value chains for industrial products were developed and validated for four industrial microalgal strains. Both single product value chains (SP) and multiproduct value chains (MP) were evaluated for their techno-economic performance and cost-revenue optimization was undertaken.…”
Section: Techno-economic Viability Of Microalgal Biorefineriesmentioning
confidence: 99%
“…Plants also offer the enticing possibility of coupling biochemical production directly to the assimilation of light energy and carbon via photosynthesis; truly green chemistry ( Sørensen et al., 2022 ). Recent thorough techno-economic analyses have shown that bio-fuel manufacturing in photosynthetic algae can be economically viable given optimal environmental conditions, especially if co-products such as protein can be extracted in parallel from the same strain ( Roles et al., 2021 ; Karan et al., 2022 ). This offers hope that with proper design and optimization, production of high value molecules through metabolic engineering in plants could prove economically feasible in the future.…”
Section: Introductionmentioning
confidence: 99%